SELF EFFICACY MAHASISWA DALAM MENGIKUTI PROGRAM PERTUKARAN MAHASISWA MERDEKA BATCH 3 - Nurazizah Rahmi; Triandini Triandini; Wulan Sari; Ginung Pratidina; Cecep Wahyudin (Governance, 2024)
This research is a qualitative descriptive study which aims to determine the self-efficacy or level of self-confidence of students participating in the PMM 3 program. The subjects in this research were 66 students participating in the PMM 3 program at Djuanda University who came from 35 universities from various islands in Indonesia, namely, Sumatra, Kalimantan, Sulawesi, NTT and NTB. The sample used was 40 respondents using the TARO YAMANE calculation. The technique used in collecting data is a survey using a self-efficacy questionnaire compiled based on Bandura indicators, namely, 1) Personal Experience (Mastery Experience), 2) Other People's Experience (Various Experience), 3) Verbal Approach (Verbal Persuasion), 4) Index Psychology (Psychological Index). The data collected was then categorized into three classifications, namely low, medium and high. The research results show that the majority of students participating in PMM 3 fall into the medium category. A total of 30 students participating in the PMM 3 program had moderate category self-efficacy. Meanwhile, the remaining 9 students had high category self-efficacy and 1 was in the low category.